"Dads are there, they are not gone missing.": The Role and Involvement of Fathers/Dads in the Lives and Education of Children with Special Educational Needs and/or Disabilities (SEN/D) within an Early Intervention (EI) Context - Ren, Ke (Trinity College Dublin. School of Education. Discipline of Education, 2023)
For families of young children with special educational needs and/or disabilities (SEN/D), the role and involvement of fathers/dads in such a parenting context does not appear to be of much research interest. Regardless of the significant role that fathers/dads can play in children?s development and education, mothers/mums continue to be seen as the primary focus and are often the exclusive participants in research relating to education for young children with SEN/D, particularly within the context of early intervention (EI). The current research programme aims to bridge this gap in knowledge and understanding of (i) fathers?/dads? experience of, perceived barriers to, and preferences for EI services; (ii) EI professionals? perceptions and their roles in promoting fathers?/dads? participation; and (iii) mothers?/mums? perceptions towards fathers?/dads? involvement in the lives of children with SEN/D. An exploratory qualitative approach was employed involving both semi-structured face-to-face interviews and telephone interviews with seven fathers/dads who have participated in EI service in Ireland, three EI professionals, and five mothers/mums. All the interviews were recorded, transcribed verbatim, subjected to thematic analysis. Findings revealed a significant gap in knowledge, views, and relationships among fathers/dads, EI professionals, and mothers/mums towards the issue that is under investigation. Importantly, several barriers and preferences for father/dad-friendly services were identified (e.g., gendered nature of EI service, father/dad-led group, activity-based intervention). Further findings and recommendations are discussed in terms of their theoretical, methodological, and empirical implications. Directions for future research are identified at both a national and international level. The findings of this research programme enhance our understanding not only of fathers?/dads? unique perspective, but also of the family unit and professionals who are critically involved in an EI context. This is critical in supporting EI professionals in Ireland to develop initiative services for fathers/dads who might be struggling in such parenting context, as well as to maximise of the experiential and educational outcome for families and their children with SEN/D. Furthermore, as the research was planned in a manner that may be understood as demonstrating applied contributions to the United Nations (UN) Sustainable Developmental Goals (SDGs) (UN General Assembly, 2015), and to have direct influence on policy, practice, experiences, and outcomes, further contribution to knowledge in the area of education for young children with SEN/D will be also made, not just in Ireland but also across Europe. Such contribution would facilitate the realisation of SDGs (e.g., Goal 4: Quality Education) in the international development community.
APPROVED
Keywords: Father/Dad involvement; Children with disabilities; Early intervention